ANALISIS PENGGUNAAN BAHASA DAERAH DALAM PEMBELAJARAN MENULIS CERPEN DI KELAS IX SMPN 1 CIPATAT KABUPATEN BANDUNG BARAT - Arifah Nurjannah; Alfa Mitri Suhara (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Regional languages often dominate students in learning activities. One of them is learning activities about writing short stories, resulting in many mistakes made by students in writing. Thus this research was held to determine the errors, causes, and influences caused by regional languages. The method in this study is quantitative descriptive, which explains the phenomenon of using numbers with a sample of 34 people. Based on research, it is known that most mistakes are errors in vocabulary usage. This means there is a large influence of regional languages, especially in writing short stories in learning activities. When this error is allowed, it will certainly damage the rules of the Indonesian language that already have standard rules.